The Contingent Nature of Public Policy and the Growth of U.S. Commercial Banking - Marquis, Christopher; Huang, Zhi (Academy of Management Journal, 2009)
That public policy affects organizational behaviors is well accepted, but less explored is how these effects may depend on other external environmental factors. We investigated policy as a necessary, but not sufficient, condition for understanding the growth of commercial banking in the United States, 1896–1978. We highlight a trade-off for banks between centralized and dispersed growth strategies and show that which strategy prevails depends on how policy enabling branching interacts with technological, economic, and cultural environments. Our findings contribute to understanding the contingent effects of policy on organizations and on the growth of large corporations in the 20th century.